Effects of dietary weight loss with and without exercise on interstitial matrix turnover and tissue inflammation biomarkers in adults with knee osteoarthritis: the Intensive Diet and Exercise for Arthritis trial (IDEA). Issue 11 (November 2017) - Loeser, R.F.; Beavers, D.P.; Bay-Jensen, A.C.; Karsdal, M.A.; Nicklas, B.J.; Guermazi, A.; Hunter, D.J.; Messier, S.P.
Summary: Objective: To examine the effects of dietary weight loss, with and without exercise, on selected soluble biomarkers in overweight and obese older adults with symptomatic knee osteoarthritis (OA). Design: Blood samples were analyzed from 429 participants in the Intensive Diet and Exercise for Arthritis (IDEA) trial randomized to either an 18 month exercise control group (E), weight loss diet (D), or D + E. C1M, C2M, C3M and CRPM biomarkers and interleukin-6 (IL-6) were quantitated using ELISAs. Radiographic progression was defined as a decrease in joint space width of ≥0.7 mm. Statistical modeling of group means and associations used mixed models adjusted for visit, baseline body mass index (BMI), gender, and baseline values of the outcome. Results: Compared to the E control group, C1M was significantly lower in the D and D + E groups at both 6 and 18 months while C3M was significantly lower in D and D + E at 6 months and in D + E at 18 months. C2M did not change in any group. Using data from all groups, change in C1M ( P  < 0.0001), C3M ( P  < 0.0001), as well as CRPM ( P  = 0.0004) from baseline to 18 months was positively associated with change in weight. No marker was associated with change in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain or radiographic progression. C3M ( P  = 0.008) and CRPM ( P  = 0.028) were positively associated with change in WOMAC function. Change in IL-6 was positively associated with change in C1M, C3M, and CRPM. Conclusion: Overweight and obese adults with knee OA who lost weight from diet and diet plus exercise reduced serum markers of interstitial matrix turnover and inflammation but not type II collagen degradation.